Upaya Penguatan Karakter Remaja Positif dengan Penyuluhan Kesehatan Remaja Bebas NAPZA - Avia, Imelda; Wijaya, Indra; Usman, Ardi; Ramadhani, Lecya Bella; Wahyudin, Wahyudin (Universitas Pahlawan Tuanku Tambusai, 2025)
Drug abuse among adolescents is a serious problem that has an impact on physical, mental, and social health. This community service activity aims to increase adolescent knowledge about the dangers of drugs and build positive character at SMA N 1 Sukatani. The method used is participatory counseling with audiovisual media, as well as knowledge evaluation through pre-test and post-test. The results showed an increase in knowledge scores after counseling, which indicates the effectiveness of this approach. Active student participation and school support strengthened the success of the activity. The importance of these results shows that periodic school-based education can be an effective preventive strategy in preventing drug abuse among adolescents. This activity contributes to the formation of a healthy and risk-aware young generation.